2021
DOI: 10.1038/s41598-021-98531-6
|View full text |Cite
|
Sign up to set email alerts
|

CCL3L3-null status is associated with susceptibility to systemic lupus erythematosus

Abstract: The correlation between copy number variation (CNV) and the susceptibility to systemic lupus erythematosus (SLE) has been reported for various immunity-related genes. However, the contribution of CNVs to SLE susceptibility awaits more investigation. To evaluate the copy numbers in immunity-related genes such as TNFAIP3, TNIP1, IL12B, TBX21 (T-bet), TLR7, C4A, C4B, CCL3L1, and CCL3L3, the modified real competitive polymerase chain reaction (mrcPCR) assay was employed, and the association between the copy number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…36 LAP3 has not been reported to be associated with SLE. Studies have found that the upregulation of LAP3 gene expression in patients with Sjogren's syndrome is associated with the deletion of copy number variation (CNVs) on chromosome 4, and CNV is associated with SLE susceptibility, 37 such as tumor necrosis factor (TNF) on chromosome 6 and small RNA-binding exonuclease protective factor La (SSB) on chromosome 2. This suggests that chromosome CNV deletion may affect the expression of the LAP3 gene.…”
Section: Discussionmentioning
confidence: 99%
“…36 LAP3 has not been reported to be associated with SLE. Studies have found that the upregulation of LAP3 gene expression in patients with Sjogren's syndrome is associated with the deletion of copy number variation (CNVs) on chromosome 4, and CNV is associated with SLE susceptibility, 37 such as tumor necrosis factor (TNF) on chromosome 6 and small RNA-binding exonuclease protective factor La (SSB) on chromosome 2. This suggests that chromosome CNV deletion may affect the expression of the LAP3 gene.…”
Section: Discussionmentioning
confidence: 99%